THE ROLE OF FOOD INVENTORY IN CONTROLLING OPERATIONAL COSTS AT HOTEL VILLA LUMBUNG - Andika, Ni Kadek Windi; Crisna Wijaya, Gede (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The Role of Food Inventory in Controlling Operational Costs at Hotel Villa Lumbung aims to understand more deeply the role of food inventory in controlling operational costs as a limitation in the implementation of writing. This writing is qualitative. The method of data collection is conducting in-depth interviews, observation, and documentation in the process of collecting data with resource persons. The location chosen in the implementation of this writing is Hotel Vila Lumbung which is located in Petitenget. From the writing that was carried out, the results showed that the role of inventory in controlling operational costs at Hotel Vila Lumbung has a very important role because Inventory determines the number of costs (Costs) that will occur. However, in terms of its implementation, it is quite simple, and the application can still be further developed along with the development of the company going forward which is adjusted to the needs that can provide progress for business development in the future.